(untitled) (Revista LIDER, 2020)
During the last 40 years, Ecuador has based its economy on extractive activities, mainly in Amazonia where there are fossil resources. Industrial practices have had negative effects. The results from a survey about vulnerabilities and capacities against the impacts of petroleum activities suggests a difficult social construction of the sanitarian risk, due to the numerous perceptions, local economic dependencies and an insufficient commitment from public actors with this issue.